Moderating Role of Price on Perceived Value and Purchase Intentions in Personal Care Products (International Journal of Scientific Research in Science and Technology, 2025)
The moderating role of price on perceived value and purchase intentions in personal care products is a multifaceted topic that involves understanding how price influences consumer perceptions and their subsequent purchasing decisions. Price can act as a signal of quality, a determinant of perceived value, and a factor in brand image, all of which contribute to purchase intentions. The relationship between price, perceived value, and purchase intentions is complex and can be influenced by various factors such as brand familiarity, price fairness, and consumer perceptions of value. Below, the key aspects of this relationship are explored.